The deployment of fiscal policy in several asean countries in dampening the impact of COVID-19 / Mohd Rozaimy Ridzuan and Noor Amira Syazwani Abd Rahman - Ridzuan, Mohd Rozaimy; Abd Rahman, Noor Amira Syazwani (Universiti Teknologi MARA, 2021)
The COVID-19 crisis is casting a long shadow over ASEAN and its member states. The number of individuals infected by it is continued to surge daily. COVID-19 has rapidly morphed into unprecedented health, economic and geopolitical crisis. Among the sectors that have practically ground to a halt are the tourism, aviation and travel sectors. This paper attempts to examine the initiatives taken by several ASEAN countries in mitigating the impact of COVID-19. A comparative analysis of the economic stimulus packages of selected ASEAN countries were analysed in order to dampen the effect of COVID-19. To make evident this statement, several evidences are presented in this paper by referring to published data, and information from secondary sources such as scholarly articles and journals, newspapers and data from the web. The findings were also strengthened by connecting those initiatives with a political economy theory of fiscal policy. The study found that the majority of ASEAN countries employ fiscal policy in order to stimulate the economy and encourage full employment.